Pemphigus vulgaris as an immune-related adverse event in recurrent metastatic esophageal squamous cell carcinoma treated with ipilimumab plus nivolumab: a case report and literature review - Nakamura, Hajime; Shionoya, Aika; Arihara, Yohei; Hayasaka, Naotaka; Kubo, Tomohiro; Usami, Makoto; Sugita, Shintaro; Uhara, Hisashi; Takada, Kohichi (Frontiers in Immunology, 2023)
Ipilimumab plus nivolumab therapy is approved for patients with unresectable advanced esophageal squamous cell carcinoma (ESCC). Although a combination of immune checkpoint inhibitors (ICIs), compared to conventional chemotherapy, can improve overall survival in patients with advanced ESCC, this increases the incidence of immune-related adverse events (irAEs). Here, we describe an ESCC case that developed pemphigus vulgaris (PV), an extremely rare cutaneous irAE, during ipilimumab plus nivolumab treatment. The patient achieved a partial response to treatment. The PV was successfully managed after the cessation of ipilimumab and the use of a topical steroid.We should thus re-treat ESCC with nivolumab monotherapy. In the era of ICIs as standard cancer therapeutics, diagnostic criteria for blistering diseases need to be established to properly manage patients with cutaneous irAEs.